1994
DOI: 10.1002/pca.2800050208
|View full text |Cite
|
Sign up to set email alerts
|

Desorption chemical ionization mass spectrometry of C‐glycosylflavones

Abstract: Seventeen natural C‐glycosylflavones have been analysed using positive desorption chemical ionization mass spectrometry with ammonia as reagent gas. This technique provides the molecular weight, information for the identification of the aglycone, the sugar sequence, and the characterization of the C‐sugar (hexose, pentose). The distinction between mono‐C‐glycosylflavones, di‐C‐glycosylflavones, C‐glycosylflavone 2″‐O‐glycosides, and di‐C‐glycosylflavone 2‴‐O‐glycosides is also obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 13 publications
1
12
0
1
Order By: Relevance
“…The short LC retention times, resistance to acid hydrolysis and absence of the aglycone ion in the firstorder MS, suggested that 6 and 9 were flavone Cglycosides. The characteristic losses of 90 and 120 amu from the pseudomolecular ions were also observed by Bakhtiar et al (1994) for flavone C-glycosides after positive desorption chemical ionisation MS and they explained them as fragments originating by cleaving specific parts of the C-sugars. According to their data, the fragments of 6 indicate it is a di-C-hexoside and those of 9 that it is a mono-C-hexoside.…”
Section: Apigenin C-glycosides (6 and 9)mentioning
confidence: 78%
“…The short LC retention times, resistance to acid hydrolysis and absence of the aglycone ion in the firstorder MS, suggested that 6 and 9 were flavone Cglycosides. The characteristic losses of 90 and 120 amu from the pseudomolecular ions were also observed by Bakhtiar et al (1994) for flavone C-glycosides after positive desorption chemical ionisation MS and they explained them as fragments originating by cleaving specific parts of the C-sugars. According to their data, the fragments of 6 indicate it is a di-C-hexoside and those of 9 that it is a mono-C-hexoside.…”
Section: Apigenin C-glycosides (6 and 9)mentioning
confidence: 78%
“…The mass spectrum of this compound showed a molecular ion at m/z 433 nm, releasing a wide range of MS 2 fragments, one of them at m/z 271, related to apigenin, and others at m/z 283, 313 and 343, which correspond to the losses of 150, 120 and 90 mass units. These fragments are due to the cross-ring cleavages that occurred in the sugar unit and are characteristic of the flavone C-hexoses (Bakhtiar et al, 1994;Sanchez-Rabaneda et al, 2003). This assumption was corroborated by the losses of one, two and three water moieties (fragments at m/z 415, 397 and 379) that are more intense than the ions resulting from the sugar cleavage (Grayer et al, 2000).…”
Section: Phytochemical Characterizationmentioning
confidence: 79%
“…In contrast, in the MS 2 spectra of mono‐ C ‐glycosides, product ions from cleavage of the sugar moiety were observed but the aglycone product ions not found, and losses of 90, 120 and 150 Da for hexose residues were taken as the main characteristics 22, 28, 29. In most cases, [M±H−90] ± , [M±H−120] ± , [M±H−134] ± and [M±H−150] ± were taken as 0,3 X ± , 0,2 X ± , 1,5 X ± , and 0,1 X ± or [ 0,2 XCH 2 O] ± ,19, 30–32 respectively. Pereira et al 19.…”
mentioning
confidence: 99%